Commentaries for Christian formation : Proverbs - Goldingay, John (Grand Rapids, MI. W.B. Eerdmans Publishing Company, 2023)
'A theological commentary on the book of Proverbs'--
Introduction. Proverbs as a theological work -- The composition of Proverbs -- Proverbs as scripture -- Commentary. Proverbs A (Proverbs 1:1-9:18) -- Proverbs B (Proverbs 10:1-22:16) -- Proverbs C (Proverbs 22:17-31:31) -- Conclusion. Actions and consequences -- Proverbs in the context of the Scriptures -- Virtue.
Includes bibliographical references (pages 431-434) and indexes.
Keywords: Bible. -- Commentaries; Commentaries